Menanamkan Pendidikan Agama Dalam Menghafal Al-Qur’an Untuk Anak Sebagai Jembatan Orang Tua Menuju Surga - Rokhmatul Hikmat; Didin Nurul Rosidin (JURNAL DIMENSI PENDIDIKAN DAN PEMBELAJARAN, 2022)
Instilling religious education in children is the first step to instill faith in the child's soul. As stated in Islamic teachings, the moral virtue of a child is greatly influenced by the guidance and education provided by parents. The purpose of this study is to provide awareness and reference for parents to instill religious education in memorizing the Qur'an in children as a bridge to heaven. The research method used is literature study. Data collection is carried out by conducting a review study of the literature that has to do with the topic to be discussed. The results obtained in the discussion and discussion are that there are several ways to instill religious education in memorizing the Qur'an as explained by Q.S. Ali-Imran verses 35-37 of which are creating intentions from both parents, praying and endeavoring. In addition, Ahsin W. Al-Hafidz suggested several methods for memorizing the Qur'an including the wahdah method, the kitabah method, the sima'i method, the combined method, and the jama' method. In its application, of course, parents need to understand the process of fostering children in all age ranges, especially at an early age.